PENGARUH LOKASI, PROMOSI DAN BAGI HASIL TERHADAP MINAT MASYARAKAT MENJADI ANGGOTABMT UGT NUSANTARA CABANG GLENMORE - Susanti, Nawal Ika; Inayah, Nurul; Hermintari, Novia (Jurnal Ekonomi Syariah Darussalam, 2022)
This research is motivated by the existence of a location close to the crowd and holding promotional activities, the public will know what is offered by the Islamic financial institution and will increase public interest in joining as members. The purpose of this study was to determine the effect of location, promotion and profit-sharing factors partially on the interest of the people who are members of BMT UGT Nusantara Glenmore Branch and the magnitude of the influence of location, promotion and profit sharing on public interest in becoming members of BMT UGT Nusantara Glenmore Branch. This study uses a quantitative approach. The data collection technique used a questionnaire using random sampling technique, the data analysis technique used was validity test, reliability test, normality test, multiple linear regression analysis T test, F test and coefficient of determination. Furthermore, the data is processed using SPSS 23.0 software. Hypothesis testing using t-test and f-test shows that: (1) location variable has a positive and insignificant effect on public interest in becoming members at BMT UGT Nusantara Glenmore Branch. (2) Promotion variable has a positive and significant effect on public interest in becoming a member of BMT UGT Nusantara Glenmore Branch. (3) the profit sharing variable has a positive and significant effect on public interest in becoming a member of BMT UGT Nusantara Glenmore Branch. (4) Promotion and profit sharing have an effect of 60.3% on the interest of the people who are members of BMT UGT Nusantara Glenmore Branch.